Identification of Shrimp From Mangrove Ecosystem, Madong Village Waters, Kampung Bugis Village, Tanjungpinang City, Riau Islands Province. - Santrina Banjarnahor; Eddiwan Eddiwan; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in the waters of the village of Kampung Madong, Kampung Bugis Village, Tanjungpinang City, Riau Islands Province. The aim are to identify Shrimp that come from mangrove ecosystem habitats from the waters of Madong Village. There werw 3 sampling areas, upstream (St 1), middle (St 2) and downstream (St 3), of the mangrove ecosystem. Prawns sampling were conducted once/week for a month period, using a spear and bubu. Morphometrical and Morphological characteristics of the prawns were analyzed descriptively and the prawns sampled were identified. The results found that there were two types of shrimp included in the Penaedae family of the genus Penaeus that live in the habitat of the mangrove ecosystem, namely (1) Panaeus monodon and (2) Panaeus merguensis. Detail identification showed that they were Panaeus monodon(37 specimens, 17 males and 20 females) andPanaeus merguensis(42 specimens, 20 males and 22 females).The waters parameters measure in mangrove ecosystem that is dissolved oxygen 7,3-8,1 mg/L, temperature 28-30oC, clarity148-190,5 cm, salinity 25-30 mg/L, pH 6,5-7,5, O27,3-8,1 mg/ l, alkalinity 52-100 mg/l. Keywords: Kampung Madong, Shrimp, Mangrove, Panaeus monodon, Panaeus merguensis